Diversity of orchids in Gunung Jerai, Kedah, Malaysia - Auyob, Nur Adilah (2016)
As one of the isolated mountains in Malaysia, Gunung Jerai, Kedah served beautiful scenery to visitors and potentially to be developed as an eco-tourism park in Kedah. Activities such as amenity forests, camping sites and outdoor sports can cause destruction to natural habitat. Geologically, the formation involved granites as the core and quartzite covers the outer layer of the mountain. This indicates the establishment of hill heath forest vegetation, mostly on the summit region and lowland dipterocarp forest vegetation at lower region. The uniqueness of its vegetation attracts botanists and collectors to do series of plant collection since 1845. Orchid’s collection has started since 1924 by Ridley and continued by others until today. Although it has been collected for almost 100 years, there is no intensive study on the diversity of orchids in Gunung Jerai, Kedah. They just produced checklists based on the species collected. Therefore, this study is needed to reveal the current orchid diversity within this area towards a proper scientific documentation apart from adding new information to the existing data. The construction of taxonomic keys is essential as reference for future studies especially in the similar type of habitats. Another objective is to propose a conservation plan for the orchids through conservation assessments especially for rare and endemic species. As to complete the sampling works, the whole mountain is divided into five zones with fourteen accessible trails. Ten metres width belt-transects are plotted along each trail. As a result, a total of 136 species are collected from five subfamilies which represented by 65 genera in Orchidaceae. From the total collection, there are 57.0 % epiphytic orchids, 34.0 % terrestrial orchids, 7.0 % lithophytic orchids and only 2.0 % are saprophytic orchids. The domination of Epidendroideae subfamily in all zones shows that it has high adaptation ability in all different types of habitat. Although sampling is done within only 0.3 % from the total area of 85.6 km2, 24 new records to Kedah are documented including three new records to Malaysia, namely Coelogyne chrysotropis, Liparis geophila and Pteroceras teres. In addition, two new species are listed and yet to be described from genera Corybas and Zeuxine. Out of fives zones, Zone 3 harbours the most species richness (88 species) and obtained the highest Simpson’s Index of Diversity (1- D = 0.890). Sorenson’s Similarity Coefficient shows there is close relation between Zone 2 and 3 as they have the highest value (Cs = 0.382) . Meanwhile, there is 67.0 % dissimilarity of species distribution between sunrise area and sunset area. As for conservation, there are 21 species categorized as vulnerable species. Then, through Species Rarity Rank, Zone 3 has the highest priority to be conserved (RT = 38). From the overall results, obviously Gunung Jerai possesses majority of habitat-specific species with 71 species (52.0 %) are determined as unique species. Thus, status of the forest needs to be changed from Rank 2 to Rank 1 to protect species and their natural habitat. Besides that, strong enforcement from Department of Forestry also needed to prohibit illegal poaching activities that can cause species extinction in wild.